Comparison of Conventional Hydroponic Nutrient Film Technique (NFT) and Smart System Based on Internet of Things (IoT) in the cultivation of Bok Choy (Brassica rapa L.) Variety Nauli F1. - Maulana, Rosihan Husnu; Devy, Lukita; Gustian, Widar Dwi; Dwiyanti, Hanifah; Nurhadiyanta, Nurhadiyanta; Kresna, Daniel (MUNISI: Military Mathematics and Natural Sciences, 2025)
Decrease of agricultural land due to increasing population, agricultural land conversion especially in urban communities lead to the use of technology for increasing the efficiency of cultivation practices. Modern agriculture or Smart Farming which utilized the use of automation and Internet of Things (IoT) is considered as one of the solutions for that purpose. This study aims to examine the comparison of Nutrient Film Technique (NFT) hydroponic using conventional and smart systems for the growth and yield of bok choy (Brassica rapa L.). Observations conducted on plant height, leaves number, SPAD, leaf color, plant width and plant weight 2 times a week for 4 weeks. Environmental observations were made on air temperature, water temperature, air humidity, pH and Total Dissolved Solution (TDS) 3 times a week for 4 weeks. Data analysis was carried out using T test. The Autonomus Monitoring and Controlling System (AMCS) was used in this study. The smart system monitored and controlled the pH and TDS, and environmental conditions using Internet of Things. Result showed that the smart system was able to monitor and control bokchoy requirements according to the range of references given. The test results showed that bok choy growth was not significantly different between the two systems. Further studies on biological and environmental aspect of more precise bok choy nutrition and microclimate requirements need to be conducted for better result.